Implementation Analysis of AES-256 and SHA-256 in EOF Steganography - Indrayani, Rini (International Journal of Informatics and Computation, 2026)
The rapid advancement of information technology has increased the demand for data security mechanisms that not only provide strong cryptographic protection but also conceal the existence of sensitive information. This study proposes a multi-layered security scheme that integrates cryptography and steganography to protect secret messages. The process begins by encrypting plaintext using the AES-256 algorithm, where the encryption key is generated from a 256-bit SHA-256 hash function. The resulting ciphertext is then embedded into digital media using the End-of-File (EOF) steganography method. Experimental results demonstrate that SHA-256 consistently produces a 32-byte output suitable for secure key generation, while AES-256 effectively transforms plaintext into ciphertext through a block-based padding mechanism, ensuring data confidentiality before embedding. Furthermore, the EOF method successfully hides the ciphertext within various file types without altering their visual appearance or primary functionality, although the file size increases proportionally to the embedded message. Thus, the integration of SHA-256, AES-256, and EOF steganography provides an effective and practical approach to multi-layered data security.The rapid advancement of information technology has increased the demand for data security mechanisms that not only provide strong cryptographic protection but also conceal the existence of sensitive information. This study proposes a multi-layered security scheme that integrates cryptography and steganography to protect secret messages. The process begins by encrypting plaintext using the AES-256 algorithm, where the encryption key is generated from a 256-bit SHA-256 hash function. The resulting ciphertext is then embedded into digital media using the End-of-File (EOF) steganography method. Experimental results demonstrate that SHA-256 consistently produces a 32-byte output suitable for secure key generation, while AES-256 effectively transforms plaintext into ciphertext through a block-based padding mechanism, ensuring data confidentiality before embedding. Furthermore, the EOF method successfully hides the ciphertext within various file types without altering their visual appearance or primary functionality, although the file size increases proportionally to the embedded message. Thus, the integration of SHA-256, AES-256, and EOF steganography provides an effective and practical approach to multi-layered data security.